The Management of Vocational High School Curriculum Implementation Based on Islamic Boarding Schools: (A Study at Manbaul Ulum Vocational School in Cirebon, Ciwaringin of Cirebon Regency, Bina Insan Mandiri in Cirebon) - Nurmalasari, Nurmalasari; Badrudin, Badrudin; Zaqiah, Qiqi Yuliati; Nursobah, Asep (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study examines a model of curriculum integration rooted in Pesantren (Islamic boarding school) principles across three Vocational High Schools (VHSs) in Cirebon Regency: VHS Manbaul Ulum, VHS Ciwaringin, and VHS Bina Insan Mandiri. The research explores how national curriculum standards, vocational competencies, and Islamic educational values are designed, implemented, and managed to produce graduates with both technical proficiency and strong Islamic character. A qualitative case study method was employed, utilizing observations, interviews with teachers, Kyai, principals, and Pesantren administrators, and curriculum documentation. Analysis focused on the planning, implementation, supervision, and evaluation of the integrated model. Results indicate that integration was achieved through stakeholder collaboration, with an organizational structure promoting synergy between vocational and Islamic education. Instructional activities combined vocational learning with Pesantren practices such as religious study, memorization, and daily moral formation. Regular evaluations involved feedback from parents and industry partners. While the model effectively nurtured religious-professional graduates, challenges included academic overload, limited student rest, scheduling issues, and insufficient teacher preparation for integrated instruction. This study contributes to developing a Pesantren-based curriculum management framework, supporting the advancement of holistic and competitive vocational education in Indonesia.